2017
DOI: 10.1371/journal.pone.0170890
|View full text |Cite
|
Sign up to set email alerts
|

Using data from the Microsoft Kinect 2 to determine postural stability in healthy subjects: A feasibility trial

Abstract: The objective of this study was to determine whether kinematic data collected by the Microsoft Kinect 2 (MK2) could be used to quantify postural stability in healthy subjects. Twelve subjects were recruited for the project, and were instructed to perform a sequence of simple postural stability tasks. The movement sequence was performed as subjects were seated on top of a force platform, and the MK2 was positioned in front of them. This sequence of tasks was performed by each subject under three different postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…This allows the virtual character on the screen to mirror the movements of the user in real time. Earlier studies concluded that Kinect v2 has the potential to be used as a reliable and valid clinical measurement tool [ 17 - 19 ]. Hence, the physiotherapists can set the range of knee angle and hip angle as they usually do in the traditional rehabilitation training when they use the exercise games.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the virtual character on the screen to mirror the movements of the user in real time. Earlier studies concluded that Kinect v2 has the potential to be used as a reliable and valid clinical measurement tool [ 17 - 19 ]. Hence, the physiotherapists can set the range of knee angle and hip angle as they usually do in the traditional rehabilitation training when they use the exercise games.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the improved hardware of Kinect 2.0, and higher accuracy, typically less than 2 mm within 2 m object-to-sensor distance [ 18 ], the Kinect 2.0 was used in this work. There are many application examples of the Kinect 2.0: biomedical engineering [ 19 , 20 , 21 ]; indoor mapping [ 22 ] and structural deformation measurement [ 23 ].…”
Section: System Design Prototype Mathematical Models and Algorithmentioning
confidence: 99%
“…The measurement abilities of the first-generation Kinect (K1) have been established for UE movements, spatiotemporal gait variables, standing balance, postural control, and even static foot posture [ 9 , 10 , 13 , 14 , 15 ]. The abilities of the second-generation Kinect (K2) are not as robustly established, but have been investigated for some UE, gait, and postural movements [ 11 , 16 , 17 ]. A recent study within our laboratory found both sensors to be valid relative to the gold standard of a VMC system when measuring reaching (forward and side) and angular shoulder movements (frontal, transverse, sagittal) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%